2015
DOI: 10.1515/libri-2014-0162
|View full text |Cite
|
Sign up to set email alerts
|

Perception and Adoption of Change Management in Information Institutions: A Study from Croatia

Abstract: This paper explores the way in which professional staff employed in information institutions perceive changes and different aspects of change management. The research focuses on Croatian libraries, museums and archives, as public and non-profit organizations. The influence of five background variables (institution, gender, age, level of education, and position) was examined in the analysis. The results show that professionals are only partially satisfied with the changes in their institutions. The type of inst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 80 publications
0
5
0
1
Order By: Relevance
“…Inisiatif perubahan adalah kegiatan yang dilakukan untuk memindahkan organisasi dari keadaan saat ini ke keadaan lain yang sering disebut sebagai visi atau keadaan yang diinginkan. Untuk mencapai keadaan yang diinginkan dibutuhkan perubahan dalam perilaku, nilai, sistem, dan struktur (Duki, 2015).…”
Section: Tinjauan Pustaka Change Managementunclassified
“…Inisiatif perubahan adalah kegiatan yang dilakukan untuk memindahkan organisasi dari keadaan saat ini ke keadaan lain yang sering disebut sebagai visi atau keadaan yang diinginkan. Untuk mencapai keadaan yang diinginkan dibutuhkan perubahan dalam perilaku, nilai, sistem, dan struktur (Duki, 2015).…”
Section: Tinjauan Pustaka Change Managementunclassified
“…Mathew 23 in his study observed a positive attitude among library professionals towards the application of IT in the Libraries to improve its services and activities, while as the need is to promote the ICT skill among the library professionals and introducing IT curriculum among the potential library professionals can help a great deal. Rahman 24 pointed out that putting in place the IT infrastructure and continuing education is imperative for the better job satisfaction and improved services and so should library professionals omit it show a more proactive approach towards embracing the technology 25 . The professionals have to always show a positive attitude towards their work and so is there need to motivate the employees towards the change which may be warranted.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The development of a new training or information literacy program, however, would meet the definition, as it would require reference staff to undertake various project management stages to be successful. Examples of library projects often consist of the introduction of new information systems, such as integrated library systems, websites or portals, the development of new facilities, the relocation of materials and staff from one facility to another, or the development of new strategic plans for the library (Dukic´, 2015;Dulock & Long, 2015;Du Plessis & Mabunda, 2016;Kinkus, 2007;Olney, Backus, & Klein, 2010;Stewart-Mailhiot, 2015). Project management is generally described in terms of both phases or processes and knowledge areas which have been defined by bodies such as the Project Management Institute through their PMBOK Guide and the Association of Project Management with their APMBOK (Greene, 2010;Kinkus, 2007;Wamsley, 2009).…”
Section: Defining Project Managementmentioning
confidence: 99%
“…A change initiative is a project undertaken to move an organization from the current state to another state À often referred to as the vision or desired state. Achieving a desired state may require changes in behaviors, values, systems, and structures (Dukic´, 2015). Any of the examples of projects in libraries listed above could also be change management initiatives because they all impact the way that employees work and interact with their patrons or communities.…”
Section: Defining Change Managementmentioning
confidence: 99%